Benefit-risk assessment: balancing the benefits and risks of leisure. Issue 4 (2nd October 2022) - Ball-King, Laurence
ABSTRACT: In recent years recreation, sport and even children's play have been affected and, in some ways, transformed by safety concerns. Although safety is a desirable goal, it may at times impinge on personal freedoms and the contribution of these activities to health and wellbeing, and it follows that a balance needs to be struck between safety and these other sought-for goals. A difficulty has been that safety concerns are usually addressed by carrying out a risk assessment, but, so far as the commonly used methods are concerned, the benefits of an activity are not part of this process and may be undervalued or forgotten. One solution has been to go beyond conventional risk assessment to a procedure that includes consideration of benefits. However, it is fair to say that this has been a slow process, partly because it appears novel and challenging, but this essay posits that benefit-risk assessment is not a newly invented procedure but one that has been commonplace throughout history, and that only from a narrow perspective can it be considered novel. The essay goes on to discuss aspects of the benefit-risk process including its historical roots, research insights, and implications for leisure time decision-making.